Statistical Legislation : Toward a More General Framework - Khawaja, Sarmad (IMF Working Papers; Working Paper ;, 2002)
The paper outlines a general framework for statistical legislation. The implications of statistical legislation for the whole statistical system, as well as for centralized versus decentralized statistical systems, are addressed. The general framework is spelled out by identifying "essential" components of statistical legislation. The paper illustrates how these components can be applied to different country situations, and it draws attention to a number of additional topics for discussion and areas for future study in statistical legislation. It also brings together summary descriptions of the statistical legislation of a large number of countries that underlie the derivation of the essential components. It thus provides a reference for countries considering new or revised statistical legislation.